Castro de Monte Mozinho e Necrópole de Monteiras (Penafiel): a cerâmica castreja em época romana - Soeiro, Teresa (2020)
An overview of the data gathered in the excavations of the Monte Mozinho hill-fort (castro) and of Monteiras necropolis, emphasizing their importance to the interpretation of the castreja ceramics evolving already under Roman rule. This transition, that lasted for about a century, between the local ways of making and the fading away of this pottery tradition into the new Roman dynamics of (regional) standardized productions for the market and the large-scale commercial trade.